Cytotoxic Activity of Hyptis Pectinate Extracts on MCF-7 Human Breast Cancer Cells - Amalina, Nur Dina; Suzery, Meiny; Cahyono, Bambang (Indonesian Journal of Cancer Chemoprevention, 2020)
Hyptis pectinata (L.) poit, popularly known in the world as “comb bushmint” is a medicinal plant commonly used for the treatment of throat and skin inflammations, bacterial infection, pain and cancer. The objective of this research is to determine the cytotoxic and antiproliferative effect under Hyptis pectinata ethanolic extract (HPE) treatment on breast cancer cells. The effect HPE of on cytotoxicity was examined by MTT assay on MCF-7 breast cancer cells. This assay also used to determine cell proliferation over 3 days of treatment with 1.5 – 100 µg/mL HPE. HPE showed that exhibited cytotoxic effects with IC50 value of 30 µg/mL for 24 hours and changes the physiological morphology on MCF-7 cells. Interestingly, the treatment of HPE for 48 and 72 hours highly decreases cell viability on MCF-7 with dose and time-dependent manner compared to untreated cells. These results indicate that HPE has antiproliferative activities and maybe the potential to be developed as a natural chemotherapeutic agent.Keywords: Hyptis pectinata (L.) poit extract, cytotoxicity, antiproliferative, MCF-7 cells